1996
DOI: 10.1002/eji.1830260713
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal and early life immune responses to various forms of vaccine antigens qualitatively differ from adult responses: predominance of a Th2‐biased pattern which persists after adult boosting

Abstract: Induction of neonatal immune responses to vaccine antigens is believed to be of limited efficacy because of immune immaturity and particular susceptibility to tolerogenic signals during this period of life. To characterize particular features of neonatal immune responses to vaccine antigens, we assessed the capacity of BALB/c mice at different stages of immunological maturation to respond to a selection of vaccine antigens and presentation systems. Significant B and T cell responses to vaccine antigens (tetanu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
193
7
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 263 publications
(216 citation statements)
references
References 52 publications
14
193
7
2
Order By: Relevance
“…Early immunization is required to impact on this mortality, but the development of vaccines that are effective at birth is impeded by the immaturity of the immune system. [3][4][5] The antibody (Ab) responses to T-cell-independent and many T-celldependent vaccine antigens are lower in young infants when compared to older children or adults. [6][7][8][9][10] Qualitative differences in Ab responses in infants include reduced Ab avidity and repertoire, and different immunoglobulin G (IgG) subclass distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Early immunization is required to impact on this mortality, but the development of vaccines that are effective at birth is impeded by the immaturity of the immune system. [3][4][5] The antibody (Ab) responses to T-cell-independent and many T-celldependent vaccine antigens are lower in young infants when compared to older children or adults. [6][7][8][9][10] Qualitative differences in Ab responses in infants include reduced Ab avidity and repertoire, and different immunoglobulin G (IgG) subclass distribution.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been demonstrated that significant IgG responses may be induced after immunization with protein antigens (reviewed in [23]), indicating that T cell help to promote isotype switch of B cells from IgM to IgG is present already in the neonatal period of life. The IgG subclass pattern observed after early life immunization of mice is, nevertheless, characterized by a relatively high IgG1/IgG2a ratio [29,30]. This pattern reflects the Th2-biased conditions of the immune system in the newborn, shown by low production of IFN-c, but relatively high production of IL-4, IL-5 and IL-13 after immunization with TD antigens under neutral conditions [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The IgG subclass pattern observed after early life immunization of mice is, nevertheless, characterized by a relatively high IgG1/IgG2a ratio [29,30]. This pattern reflects the Th2-biased conditions of the immune system in the newborn, shown by low production of IFN-c, but relatively high production of IL-4, IL-5 and IL-13 after immunization with TD antigens under neutral conditions [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Forsthuber et al (8) demonstrated that injection of neonatal animals with protein Ags in IFA actually induces immune deviation rather than tolerance and stimulates preferential expression of Th cell type 2 (Th2) cytokines and Ab isotypes. Similarly, Siegriest and colleagues (9,10) found that neonatal vaccine immunization results in biased Th2-type responses that still remain after adult boosting. Collectively, these findings have significant implications for neonatal vaccination strategies and suggest that redirection of the neonatal immune system to a Th1 pathway might increase responsiveness to vaccine Ags.…”
mentioning
confidence: 95%